PWE-056 Management and outcomes of pregnancy in patients with inflammatory bowel disease in joint obstetric/IBD clinic. (8th June 2018) - Shahabuddin, Erum; Marley, Alexandra; Iriarte, Rolland; Bartlam, Sharon; Gornall, Adam; Townson, Gillian
Abstract : Introduction: Many women with Inflammatory Bowel Disease (IBD) are of child-bearing age and therefore managing fertility and pregnancy is, for many women, an important part of their care. While an uneventful pregnancy and a healthy baby is the norm in women with IBD, managing these complex conditions in pregnancy can be challenging. Our aim was to look at management and outcomes for pregnant patients with Crohn's Disease (CD) and Ulcerative Colitis (UC) in a District General Hospital following the implementation of a joint IBD/Obstetric clinic. Methods: Patients with IBD were identified when they booked for their maternity care between 22/2/15–16/7/16. Data was collected retrospectively via both paper notes and online electronic patient record. We obtained information regarding patients' IBD including diagnosis, medications used during pregnancy and previous surgical history. In addition, Obstetric data was collected, including method of conception, numbers of live births, miscarriage, terminations, birth weight, pre-term delivery, congenital abnormalities and maternal mortality. Results: We found that there was a higher incidence of foetal loss in our cohort after booking visit than would be expected in the general population. In our group of IBD patients only 17% of Crohn's patients underwent a caesarean section, whilst it was 50% in the UC cohort. One patient with CD delivered pre-term having stopped her anti-TNF therapy early in pregnancy against her physician's advice. 73% patients in our population delivered at term with good outcomes. Conclusions: It is important for patients to maintain remission during pregnancy by strictly adhering to their medications. Medications used for the management of IBD are safe to take during the conception period and during first two trimesters of pregnancy with the exception of methotrexate and thalidomide. Patients with IBD can be at increased risk of miscarriage.